When states appease: British appeasement in the 1930s. Issue 2 (30th September 2014) - TRUBOWITZ, PETER; HARRIS, PETER
Abstract: When do states appease their foes? In this article, we argue that governments are most likely to favour appeasing a foreign threat when their top leaders are severely cross–pressured: when the demands for increased security conflict sharply with their domestic political priorities. We develop the deductive argument through a detailed analysis of British appeasement in the 1930s. We show that Neville Chamberlain grappled with a classic dilemma of statecraft: how to reduce the risk of German expansionism while facing acute partisan and electoral incentives to invest resources at home. For Chamberlain, appeasement was a means to reconcile the demands for increased security with what he and his co-partisans were trying to achieve domestically. We conclude by discussing implications of the analysis for theorising about appeasement and about how leaders make grand strategy more generally.